Detection method for simultaneously detecting seawater-based Pb (II) and Cd (II)

By graphitizing the glassy carbon electrode modified by carboxylated multi-walled carbon nanotubes and zinc oxide composites, differential pulse voltammetry is used to detect Pb(II) and Cd(II) in seawater, the problems of difficulty and cost in the prior art are solved, and heavy metal ion detection with high sensitivity and low detection limit are achieved.

CN119715715APending Publication Date: 2025-03-28BEIBU GULF UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411898463.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to detect divalent lead ions (Pb(II)) and divalent cadmium ions (Cd(II)) in seawater simultaneously, and traditional detection methods and equipment are expensive and maintenance costs are high.

Method used

Graphitized carboxylated multi-walled carbon nanotubes and zinc oxide composites were used to modify the glass carbon electrode, and the detection was carried out by differential pulse voltammetry, and the experimental conditions were optimized to improve detection accuracy and sensitivity.

Benefits of technology

Simultaneous detection of Pb(II) and Cd(II) in seawater is realized, with the detection limits as low as 0.535μg/L and 0.354μg/L respectively, with good stability, reproducibility and anti-interference, and can detect heavy metal ions in actual seawater with high sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715715A_ABST
    Figure CN119715715A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of seawater detection, and particularly relates to a detection method for simultaneously detecting seawater-based Pb (II) and Cd (II), which comprises the following steps: step 1, polishing a glassy carbon electrode: polishing the glassy carbon electrode for three times by using aluminum oxide powder according to an 8-shaped track, then carrying out ultrasonic treatment in ultrapure water for 2-4 minutes, removing surface adhesion substances, washing by using ultrapure water, and drying to obtain the glassy carbon electrode; and activating the glassy carbon electrode in a sulfuric acid solution, scanning by using cyclic voltammetry until a stable cyclic voltammetry curve is obtained, washing by using ultrapure water, and drying at room temperature. Step 2, preparing a graphitized carboxylated multi-walled carbon nanotube solution, namely weighing 3.5 mg of graphitized carboxylated multi-walled carbon nanotubes and 0.8 mg of nano zinc oxide, dissolving the graphitized carboxylated multi-walled carbon nanotubes and the nano zinc oxide in 5ml of dimethylformamide, and performing ultrasonic dispersion for more than 3h to obtain the graphitized carboxylated multi-walled carbon nanotube solution; the method has good stability, reproducibility and anti-interference performance, and can realize high-sensitivity detection of Pb (II) and Cd (II) in actual seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of seawater detection, in particular to a detection method for simultaneously detecting seawater-based Pb (II) and Cd (II). Background Art

[0002] The ocean, which occupies about 70% of the earth's surface area, is the cradle of life and a vital component of the earth's ecosystem. However, with the continuous expansion and development of human industrial activities, the discharge of industrial wastewater, mining, and the burning of fossil fuels have caused excessive heavy metal ions to exist in the marine environment, resulting in severe challenges to the marine environment. Common heavy metals in the ocean include lead, cadmium, mercury, copper, zinc, etc. In the marine environment, pollution usually appears in a complex state. Heavy metal pollutants are not only toxic to marine organisms, but in fact, there are usually interactions, which are prone to joint toxicity. Cadmium and lead are common heavy metal pollutants. Once they enter the ocean, they will continue to accumulate in water bodies, sediments, and marine organisms. When excessive cadmium and lead enter the organism, they will have serious toxic effects on the physiological functions of marine organisms. From a microscopic perspective, they may interfere with enzyme activity in organisms and affect cell metabolism. Pb(Ⅱ) (divalent lead ions) and Cd(Ⅱ) (divalent cadmium ions) have similar chemical properties and can act on marine organisms in similar ways and pathways, thereby competing for binding sites on the cell surface and related metabolic systems. In marine organisms, the combined toxicity of heavy metals mainly works by interfering with the normal physiological and biochemical processes of organisms. It can also affect the structure and function of cell membranes, thereby changing their permeability and transport capacity. From a macroscopic perspective, the combined toxicity of Pb(Ⅱ) and Cd(Ⅱ) can cause slow growth and development of marine organisms, reduced reproductive capacity, and even induce disease and lead to death.

[0003] Joint experiments have shown that heavy metals are easily enriched and accumulated in bivalve mollusks and fish due to their non-degradability. In the acute exposure study of rainbow trout, Pb(Ⅱ) and Cd(Ⅱ) had a synergistic effect, and the absorption rate of heavy metals by the organism was significantly increased. The two metals promoted each other and showed obvious synergistic effects. The behavioral rhythm disorders caused by cadmium exposure are associated with the disorders of some circadian rhythm genes, and lead exposure can weaken the movement ability of marine organisms. In the study of Jian Yin et al., it was verified that lead and cadmium exposure caused oxidative stress and inflammatory responses in zebrafish. When zebrafish were exposed to lead and cadmium together, they had an antagonistic effect on behavioral patterns.

[0004] More importantly, marine organisms have a certain ability to accumulate cadmium and lead. These enriched heavy metals will be gradually transmitted along the food chain, and with the help of biomagnification, they will reach higher levels in organisms at higher trophic levels. Ultimately, humans, as consumers at the top of the food chain, are very likely to ingest marine foods containing high concentrations of cadmium and lead, which will cause serious harm to their own health. Humans who eat marine foods contaminated with cadmium, such as fish and shellfish, will ingest cadmium. Long-term intake may lead to cadmium poisoning in the human body, causing health problems such as kidney damage and bone lesions. The World Health Organization stipulates that the concentration of Pb (Ⅱ) in drinking water should be less than 10ug / L, and the concentration of Cd (Ⅱ) should be less than 3μg / L. Therefore, the development of a rapid, accurate and sensitive detection method is of great significance for monitoring the content of lead and cadmium in the marine environment.

[0005] There are many methods for heavy metal detection, such as atomic absorption spectroscopy, atomic fluorescence, ultraviolet-visible spectrophotometry, inductively coupled plasma mass spectrometry, etc., but the equipment is expensive and the maintenance cost is high, which will increase the detection cost.

[0006] Therefore, in order to solve the above problems, a detection method for simultaneously detecting seawater-based Pb(Ⅱ) and Cd(Ⅱ) was proposed. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In view of the shortcomings of the prior art, the present invention provides a detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) to solve the problems raised in the background technology.

[0009] (II) Technical solution

[0010] To achieve the above object, the present invention provides the following technical solution: a detection method for simultaneously detecting seawater-based Pb(II) and Cd(II), comprising the following steps:

[0011] Step 1, polishing of glassy carbon electrode: polish the glassy carbon electrode with aluminum oxide powder in an "8" shape track for 3 times, then ultrasonicate in ultrapure water for 2 to 4 minutes to remove surface adhesion and then rinse with ultrapure water, then activate the glassy carbon electrode in sulfuric acid solution, and then scan with cyclic voltammetry until a stable cyclic voltammetry curve is obtained, then rinse with ultrapure water and dry at room temperature;

[0012] Step 2, preparation of graphitized carboxylated multi-walled carbon nanotube solution: weigh 3.5 mg of graphitized carboxylated multi-walled carbon nanotubes and 0.8 mg of nano zinc oxide, dissolve them in 5 ml of dimethylformamide, and ultrasonically disperse for more than 3 hours;

[0013] Step 3, preparation of a glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide: the graphitized carboxylated multi-walled carbon nanotube solution is uniformly coated on the surface of the glassy carbon electrode by a drop coating method to form a stable composite film, and then the composite film is characterized by cyclic voltammetry, electrochemical impedance spectroscopy and scanning electron microscopy;

[0014] Step 4: Simultaneous detection of heavy metal ions: Use differential pulse voltammetry to simultaneously detect divalent lead ions and divalent cadmium ions.

[0015] Preferably, in step 1, the particle sizes of the alumina powder after three polishings are 1.0 μm, 0.3 μm and 0.5 μm respectively, the diameter of the glassy carbon electrode is 3.0 mm, and the concentration of the sulfuric acid solution is 0.5 mol·L -1 .

[0016] Preferably, in step 3, the graphitized carboxylation multi-walled carbon nanotubes can improve the conductivity of the glassy carbon electrode, zinc oxide can enhance the electronic conductivity of the glassy carbon electrode, the multi-walled carbon nanotubes themselves have a large specific surface area, and the carboxylation treatment increases the active sites, which is beneficial to the adsorption and reaction of heavy metal ions.

[0017] Preferably, in step 4, under optimal experimental conditions, the response peak current of divalent lead ions and divalent cadmium ions shows a good linear relationship with the concentration in the range of 25 to 450 μg / L, and the detection limits are as low as 0.535 μg / L and 0.354 μg / L, respectively.

[0018] Preferably, in the cyclic voltammetry electrochemical experiment, when an electrochemical reaction occurs on the electrode surface, the electroactive substance needs to diffuse from the bulk of the solution to the electrode surface. Assuming that the electrode reaction is a reversible single electron transfer process, and the concentration distribution of the electroactive substance in the solution is only affected by the diffusion process (i.e., ignoring other factors such as convection and electromigration), the basic form of the Randles-Sevcik equation can be derived through basic principles such as Fick's diffusion law and the Butler-Volmer electrode kinetic equation, as shown in the following formula:

[0019] I p =2.69×10 5 n 3 / 2 AD 1 / 2 v 1 / 2 C;

[0020] Among them, I p is the peak current, unit: A, n is the number of electrons transferred in the electrode reaction, A is the active area of ​​the electrode, unit: cm 2 , D is the diffusion coefficient of the electroactive substance in the solution, unit: cm 2 / s, C is the concentration of the electroactive substance in the solution, unit: mol / cm 3, v is the scan rate set in the cyclic voltammetry experiment, unit: V / s;

[0021] According to the above equation, the effective surface area of ​​the glassy carbon electrode can be calculated to be 0.199 cm 2 The effective surface area of ​​the ZnO-modified glassy carbon electrode is 0.288 cm 2 The effective surface area of ​​the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes is 0.414 cm 2 The effective surface area of ​​the glassy carbon electrode modified by graphitized carboxylated multi-walled carbon nanotubes and zinc oxide is 0.508 cm 2 The results show that the glassy carbon electrode composite modified material composed of graphitized carboxylated multi-walled carbon nanotubes and zinc oxide can accelerate the electron transfer rate on the electrode surface and has excellent conductive properties.

[0022] Preferably, under the optimal experimental conditions, in the acetic acid-sodium acetate solution electrolyte dissolution with pH = 6, enrichment time 300s, and enrichment potential -1.1V, the mixed sample of divalent lead ions and divalent cadmium ions is subjected to differential pulse voltammetry detection, and the linear regression equation of the response current signal in the range of 25 to 450 μg / L is Y = 0.15303X-2.8715, with a correlation coefficient of 0.99977, and the linear regression equation of the divalent cadmium ions is Y = 0.10136X-2.478, the correlation coefficient is 0.9988. The following detection limit calculation equation shows that the detection limits of divalent lead ions and divalent cadmium ions are 0.354μg / L and 0.535μg / L, respectively, which are much lower than the World Health Organization (WHO) divalent lead ion concentration of 10μg / L and divalent cadmium ion concentration of 3μg / L. The experimental results show that the electrode modified by graphitized carboxylated multi-walled carbon nanotubes and zinc oxide has a lower detection limit;

[0023]

[0024] (III) Beneficial effects

[0025] Compared with the prior art, the present invention provides a detection method for simultaneously detecting seawater-based Pb(II) and Cd(II), which has the following beneficial effects:

[0026] The present invention adopts a graphitized carboxylated multi-walled carbon nanotube and a zinc oxide composite material to modify a glassy carbon electrode. The graphitized carboxylated multi-walled carbon nanotube and zinc oxide composite material has better electronic conductivity and a larger specific surface area. A sensor for detecting seawater-based Pb(Ⅱ) and Cd(Ⅱ) is constructed. The modified electrode is characterized by a scanning electron microscope and cyclic voltammetry, and the optimal conditions are determined: a 0.1 mol / L sodium acetate solution is selected as the buffer solution, the pH is 6, the deposition potential is -1.1 V, and the enrichment time is 300 s. After optimization, under the optimal experimental conditions, Pb(Ⅱ) and Cd(Ⅱ) are detected simultaneously. The results show that Pb(Ⅱ) and Cd(Ⅱ) The response peak current of Cd(Ⅱ) shows a good linear relationship with the concentration of 25-450ug / L, and the detection limits are 0.535μg / L and 0.354μg / L, respectively. It is used for the analysis of coastal water bodies in Maowei Sea. The recovery rates of Pb(Ⅱ) are between 99.2% and 108%, and the recovery rates of Cd(Ⅱ) are between 91.6% and 106.3%; the relative standard deviation of Pb(Ⅱ) is ≤2.41%, and the relative standard deviation of Cd(Ⅱ) is ≤2.53%; based on the above experimental conclusions, the sensor has good stability, reproducibility and anti-interference, and can achieve high-sensitivity detection of Pb(Ⅱ) and Cd(Ⅱ) in actual seawater. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 It is a schematic diagram of the detection process of the present invention;

[0029] Figure 2 The present invention is a scanning electron microscope image of a graphitized carboxylated multi-walled carbon nanotube (a) at a magnification of 100kx, a zinc oxide (b) at a magnification of 100kx, a graphitized carboxylated multi-walled carbon nanotube and zinc oxide composite material (c) at a magnification of 100kx, and a graphitized carboxylated multi-walled carbon nanotube and zinc oxide composite material (d) at a magnification of 150kx;

[0030] Figure 3 The electrochemical impedance spectroscopy test diagram (a) of the glassy carbon electrode modified with carboxylated multi-walled carbon nanotubes and zinc oxide, the glassy carbon electrode modified with carboxylated multi-walled carbon nanotubes, the glassy carbon electrode modified with zinc oxide and the bare glassy carbon electrode and the cyclic voltammetry curves of different electrodes in 0.1 mol / L potassium ferrocyanide solution (b);

[0031] Figure 4The cyclic voltammetry linear comparison diagram (a) of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide in the present invention and the relationship between the peak current of the anode and cathode and the square root of the scanning speed are compared in the diagram (b);

[0032] Figure 5 It is a differential pulse voltammetry line shape comparison diagram of different electrodes in 50ug / L Pb(Ⅱ) and Cd(Ⅱ) solutions in the present invention;

[0033] Figure 6 1 is a bar graph of peak current of different buffer solutions (a) and a line graph of peak current of different pH values ​​(b);

[0034] Figure 7 The figures are a linear comparison diagram of the effects of different deposition times in the present invention (a) and a line graph of different deposition times (b);

[0035] Figure 8 1. The figure is a linear comparison diagram of the influence of different enrichment potentials in the present invention (a) and a line graph of different enrichment potentials (b);

[0036] Fig. 9 1 is a peak current linear comparison diagram (a) of different film thicknesses and a peak current broken line diagram (b) of different film thicknesses in the present invention;

[0037] Fig.10 The graphs are voltammograms (a) of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide in the present invention for dissolving divalent lead ions and divalent cadmium ions at different concentrations (25-450 μg / L) and a linear regression curve diagram (b) of divalent lead ions and divalent cadmium ions;

[0038] Fig.11 The peak current bar graph (a) of the divalent lead ion and divalent cadmium ion solutions of the present invention with 150 times the concentration of interfering ions of Cr(VI), Mn(II), Cu(II) and Zn(II) added respectively and the peak current bar graph (b) of the differential pulse stripping voltammetry detection of glassy carbon electrodes modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide composites from 5 different batches;

[0039] Fig.12 The peak current diagram (a) of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide in the present invention detected by differential pulse stripping voltammetry for 6 consecutive times and the peak current diagram (b) of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide within 30 days. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Specific examples are given below.

[0042] See also Figure 1-Figure 12 The present invention provides a detection method for simultaneously detecting seawater-based Pb(II) and Cd(II), comprising the following steps:

[0043] Step 1, polishing of glassy carbon electrode: polish the glassy carbon electrode with aluminum oxide powder in an "8" shape track for 3 times, then ultrasonicate in ultrapure water for 2 to 4 minutes to remove surface adhesion and then rinse with ultrapure water, then activate the glassy carbon electrode in sulfuric acid solution, and then scan with cyclic voltammetry until a stable cyclic voltammetry curve is obtained, then rinse with ultrapure water and dry at room temperature;

[0044] Step 2, preparation of graphitized carboxylated multi-walled carbon nanotube solution: weigh 3.5 mg of graphitized carboxylated multi-walled carbon nanotubes and 0.8 mg of nano zinc oxide, dissolve them in 5 ml of dimethylformamide, and ultrasonically disperse for more than 3 hours;

[0045] Step 3, preparation of a glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide: the graphitized carboxylated multi-walled carbon nanotube solution is uniformly coated on the surface of the glassy carbon electrode by a drop coating method to form a stable composite film, and then the composite film is characterized by cyclic voltammetry, electrochemical impedance spectroscopy and scanning electron microscopy;

[0046] Step 4: Simultaneous detection of heavy metal ions: Use differential pulse voltammetry to simultaneously detect divalent lead ions and divalent cadmium ions.

[0047] The above scheme: In the cyclic voltammetry electrochemical experiment, when an electrochemical reaction occurs on the electrode surface, the electroactive substance needs to diffuse from the solution to the electrode surface. Assuming that the electrode reaction is a reversible single electron transfer process, and the concentration distribution of the electroactive substance in the solution is only affected by the diffusion process (i.e., ignoring other factors such as convection and electromigration), the basic form of the Randles-Sevcik equation can be derived through basic principles such as Fick's diffusion law and the Butler-Volmer electrode kinetic equation, as shown in the following formula:

[0048] I p =2.69×10 5 n 3 / 2 AD1 / 2 v 1 / 2 C;

[0049] Among them, I p is the peak current, unit: A, n is the number of electrons transferred in the electrode reaction, A is the active area of ​​the electrode, unit: cm 2 , D is the diffusion coefficient of the electroactive substance in the solution, unit: cm 2 / s, C is the concentration of the electroactive substance in the solution, unit: mol / cm 3 , v is the scan rate set in the cyclic voltammetry experiment, unit: V / s;

[0050] According to the above equation, the effective surface area of ​​the glassy carbon electrode can be calculated to be 0.199 cm 2 The effective surface area of ​​the ZnO-modified glassy carbon electrode is 0.288 cm 2 The effective surface area of ​​the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes is 0.414 cm 2 The effective surface area of ​​the glassy carbon electrode modified by graphitized carboxylated multi-walled carbon nanotubes and zinc oxide is 0.508 cm 2 The results show that the glassy carbon electrode composite modified by graphitized carboxylated multi-walled carbon nanotubes and zinc oxide can accelerate the electron transfer rate on the electrode surface and has excellent conductive properties;

[0051] The electrochemical reaction process of the electrode is divided into surface process control and diffusion process control. Tests at different scan rates were carried out in 0.1M potassium chloride and 5M potassium ferrocyanide, such as Figure 4 As shown in a, it can be seen that with the increase of scanning speed, the peak current also gradually increases. Figure 4 b shows the peak current Ip and the scanning speed V 1 / 2 A certain linear relationship is shown, indicating that the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide is modified, and the reversible electron transfer process is controlled by the diffusion process.

[0052] Further Figure 1-Figure 12 As shown in step 1, the particle sizes of the alumina powder after three polishings are 1.0 μm, 0.3 μm and 0.5 μm respectively, the diameter of the glassy carbon electrode is 3.0 mm, and the concentration of the sulfuric acid solution is 0.5 mol·L -1 .

[0053] The above scheme: Polishing can remove impurities, oxides and possible contaminants on the electrode surface, make the electrode surface reach a mirror state, ensure full and uniform contact between the electrode and the electrolyte, provide a stable and consistent interface for the electrochemical reaction, and thus improve the accuracy and reproducibility of the measurement; for example, when detecting trace metal ions in the solution, if the electrode surface is not flat and smooth, the adsorption and reaction of the ions will be uneven, resulting in fluctuations in the measurement results; by polishing in an "8" shape, the active sites on the electrode surface can be fully exposed, the effective reaction area of ​​the electrode can be increased, the reaction activity and sensitivity of the electrode can be improved, the electrode can better participate in the electrochemical reaction, and the detection of low-concentration substances can be more accurate.

[0054] Further Figure 1-Figure 12 As shown, in step 3, graphitized carboxylation of multi-walled carbon nanotubes can improve the conductivity of the glassy carbon electrode, zinc oxide can enhance the electronic conductivity of the glassy carbon electrode, the multi-walled carbon nanotubes themselves have a large specific surface area, and the carboxylation treatment increases the active sites, which is beneficial to the adsorption and reaction of heavy metal ions.

[0055] The above scheme: The graphene multi-walled carbon nanotube composite material greatly increases the effective surface area of ​​the electrode, and more graphene layers are introduced into its structure, so that the π electron cloud overlap between carbon atoms is higher, thereby improving the conductivity of the material, and the carboxyl multi-walled carbon nanotube has higher reactivity and stronger adsorption capacity. The hydroxyl group can adsorb with metal ions, thereby improving the stability and compatibility of the material, and can promote the enrichment and redox reaction of the ions to be measured on the electrode surface. Therefore, the graphitized carboxyl multi-walled carbon nanotube retains the tubular structure of the multi-walled carbon nanotube and has a higher aspect ratio. After the graphitization treatment, the graphitization degree of the carbon nanotube is improved, the crystal structure is more ordered, and the electronic conductivity is further enhanced. At the same time, the introduction of the carboxyl functional group brings significant improvements in the dispersibility, chemical reactivity, biocompatibility and adsorption performance of the multi-walled carbon nanotube;

[0056] Zinc oxide has strong catalytic properties and can accelerate electrochemical reactions, but its own conductivity is relatively low. By combining with multi-walled carbon nanotubes, the overall conductivity of the electrode can be improved. The high specific surface area of ​​zinc oxide helps to form good contact with conductive materials, promote electron transfer, and improve the electrochemical performance of the electrode. Figure 3 As shown in b, the glassy carbon electrode curve modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide showed the strongest current response.

[0057] Further Figure 1-Figure 12 As shown, in step 4, under the optimal experimental conditions, the response peak current of divalent lead ions and divalent cadmium ions showed a good linear relationship with the concentration in the range of 25 to 450 μg / L, and the detection limits were as low as 0.535 μg / L and 0.354 μg / L, respectively.

[0058] The above scheme: Under the optimal experimental conditions, in the acetic acid-sodium acetate solution electrolyte dissolution with pH = 6, enrichment time 300s, and enrichment potential -1.1V, the mixed sample of divalent lead ions and divalent cadmium ions was detected by differential pulse voltammetry. The response current signal in the range of 25-450μg / L, Fig.10 a is the relationship between the peak current and the concentration of dissolution, Fig.10 b is the linear regression equation of the divalent lead ion and divalent cadmium ion concentration fitting. The linear regression equation of divalent lead ion is Y=0.15303X-2.8715, and the correlation coefficient is 0.99977. The linear regression equation of divalent cadmium ion is Y=0.10136X-2.478, and the correlation coefficient is 0.9988. The following detection limit calculation equation shows that the detection limits of divalent lead ions and divalent cadmium ions are 0.354μg / L and 0.535μg / L, respectively, which are much lower than the World Health Organization (WHO) divalent lead ion concentration of 10μg / L and divalent cadmium ion concentration of 3μg / L. The experimental results show that the electrode modified by graphitized carboxylated multi-walled carbon nanotubes and zinc oxide has a lower detection limit;

[0059]

[0060] Further Figure 1-Figure 12 As shown, from Figure 5 It can be seen that the current response of the glassy carbon electrode is relatively low. This is because the surface active sites of the pure glassy carbon electrode are limited and the promoting effect on the electrochemical reaction is weak. The introduction of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes significantly improves the current response of the electrode.

[0061] Further Figure 1-Figure 12 As shown, considering the influence of different buffer solutions, differential pulse stripping voltammetry was performed in three different electrolyte solutions, namely, 0.1 mol / L PH=6 potassium chloride, sodium acetate, and phosphate buffer solution, all containing 50 ug / L Pb(Ⅱ) and Cd(Ⅱ). The results are shown in Figure 6 As shown in a, it can be seen that the peak current is the highest in the sodium acetate acetic acid buffer solution, so we choose sodium acetate acetic acid as the subsequent electrolyte buffer solution;

[0062] When the pH of the electrolyte solution is too low, the hydrogen ions in the solution will compete with Pb(Ⅱ) and Cd(Ⅱ), and a hydrogen evolution reaction will occur on the electrode surface. The hydrogen ions will preferentially undergo a reduction reaction on the electrode surface, occupying the active sites on the electrode surface, which will inhibit the reduction reaction of Pb(Ⅱ) and Cd(Ⅱ), resulting in a decrease in the peak current. Figure 6As shown in Figure b, when pH = 4, the peak current values ​​of Pb(Ⅱ) and Cd(Ⅱ) are only 0.55A and 1.78A. When the pH of the sodium acetate electrolyte solution changes from 4.0 to 6.0, the peak current increases continuously and reaches the maximum at pH = 6.0. When the pH continues to increase, the peak current shows a downward trend. This is because when the pH is too high, the OH-hydroxyl ions present in the solution will react with the target metal ions to form complexes, resulting in a decrease in the concentration of the target metal ions. Therefore, pH = 6 is the optimal pH.

[0063] Further Figure 1-Figure 12 As shown, using an appropriate deposition potential is critical to improving sensitivity. Figure 8 a shows the effect of different enrichment potentials on the peak current, Figure 8 b It can be seen that there is a significant growth trend in the range of -0.9V to -1.1V. When the enrichment potential reaches -1.1V, the peak current is the largest, and then the peak current decreases. This is because when it exceeds -1.1V, hydrogen evolution reaction occurs on the electrode surface, generating bubbles, which hinder the deposition of Pb(Ⅱ) and Cd(Ⅱ). At the same time, the enriched Pb(Ⅱ) and Cd(Ⅱ) will also fall off from the electrode surface. The maximum dissolution peaks of the two heavy metals are both at -1.1V. Therefore, the potential of -1.1V is selected as the best condition for optimizing the experimental conditions.

[0064] At 0.1 mol·L -1 In an acetic acid and sodium acetate environment at pH 6, the effect of preconcentration time of 100s to 350s on the electrochemical response was studied by differential pulse anodic stripping voltammetry. Figure 7 It can be seen from a that from 100s to 300s, the peak currents of Pb(Ⅱ) and Cd(Ⅱ) increase rapidly. After more than 300s, the peak currents decrease. Figure 7 b It can be seen that when the deposition time is 300s, the peak current reaches the maximum, so the deposition time of 300s is selected as the optimal deposition time.

[0065] Further Figure 1-Figure 12 As shown, Fig. 9 a The effect of the modified film thickness of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide on the peak current of the current response of Pb(Ⅱ) and Cd(Ⅱ) was investigated in the range of 1 to 6 μL. Fig. 9b. It can be seen that with the increase of film thickness, the peak current gradually increases. When it reaches 5μL, the peak current reaches the maximum. When the film thickness is 6μL, the peak current begins to slow down. This is because when the film thickness is too low, its active ingredients are unevenly dispersed in the film, the electrode surface reaction is difficult, and the peak current is low. However, with the gradual increase of film thickness, too many proton transmission channels will hinder the transmission of Pb(Ⅱ) and Cd(Ⅱ). Due to insufficient adsorption capacity, electron transfer is hindered, the electrode surface reaction becomes difficult, and the peak current decreases.

[0066] Secondly, in order to further study the detection performance of seawater-based Pb(Ⅱ) and Cd(Ⅱ) sensors, the detection results of Pb(Ⅱ) and Cd(Ⅱ) by different electrodes were compared. It can be seen from Table 1 that the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide in this study has a wider detection range and lower detection limit. The results show that the system can be applied to the detection of seawater-based Pb(Ⅱ) and Cd(Ⅱ).

[0067] Table 1. Comparison of different electrodes for detection of Pb(II) and Cd(II)

[0068]

[0069]

[0070] Further Figure 1-Figure 12 As shown, in order to further explore the detection performance of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide, the interference ions of tetravalent chromium, divalent manganese, divalent copper and divalent zinc were added at 150 times to study their interference with the detection of Pb(Ⅱ) and Cd(Ⅱ) ions. The experimental results are shown in Fig.11 As shown in a, the influence of the above interfering ions on the change of the peak current of Pb (Ⅱ) and Cd (Ⅱ) is calculated to be within 5.53%. The experimental results show that the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide has good anti-interference performance. In the acetic acid sodium acetate buffer solution containing 150ug / L Pb (Ⅱ) and Cd (Ⅱ), 5 different batches of glassy carbon electrodes were used for modification and measured by differential pulse voltammetry. The experimental results are shown in Fig.11 As shown in b, the calculated change rate of the peak current is lower than 8.68%, indicating that the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide has good reproducibility.

[0071] Further Figure 1-Figure 12As shown, in order to evaluate the stability of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide, it was measured by differential pulse anodic stripping voltammetry for 6 consecutive times in an acetic acid sodium acetate buffer solution containing 150ug / L Pb(Ⅱ) and Cd(Ⅱ), as shown in FIG. Fig.12 As shown in a, the peak current change rate is calculated to be within 7.30%. At the same time, under the same experimental conditions, the DPASV measurement of the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide was carried out for 30 consecutive days. Fig.12 b It can be seen that with the increase of days, the peak current decreases slightly, but the overall trend tends to be stable. The calculation shows that the peak current change rate is within 6.64%, indicating that it has good stability.

[0072] Sample Analysis:

[0073] Maowei Sea is located in the south of Qinzhou City and is part of the Qinzhou Bay. It covers an area of ​​about 135 square kilometers and is a semi-enclosed inland sea. It is mainly fed by rivers such as Qinjiang River and Maoling River. It belongs to coastal waters. After the sample was allowed to stand for 3 days, it was filtered with a 0.45μL microporous membrane. 20mL of the filtered sample was measured for spike recovery experiment. The graphitized carboxylated multi-walled carbon nanotubes and zinc oxide composite modified electrodes were used for determination. The experimental results are shown in Tables 2 and 3. The spike recovery rates of Pb(Ⅱ) and Cd(Ⅱ) were 99.2% to 108%, and the spike recovery rates of Cd(Ⅱ) were 91.6% to 106.3%, indicating that the sensor can be used to detect the concentrations of Pb(Ⅱ) and Cd(Ⅱ) in actual samples.

[0074] Table 2 Detection of Cd(Ⅱ) concentration in actual samples

[0075]

[0076] Table 3 Detection of Pb(Ⅱ) concentration in actual samples

[0077]

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II), characterized in that: The following steps are involved: Step 1, polishing of glassy carbon electrode: polish the glassy carbon electrode with aluminum oxide powder in an "8" shape track for 3 times, then ultrasonicate in ultrapure water for 2-4 minutes to remove the surface adhesion and then rinse with ultrapure water, then activate the glassy carbon electrode in sulfuric acid solution, and then scan with cyclic voltammetry until a stable cyclic voltammetry curve is obtained, then rinse with ultrapure water and dry at room temperature; Step 2, preparation of graphitized carboxylated multi-walled carbon nanotube solution: weigh 3.5 mg of graphitized carboxylated multi-walled carbon nanotubes and 0.8 mg of nano zinc oxide, dissolve them in 5 ml of dimethylformamide, and ultrasonically disperse for more than 3 hours; Step 3, preparation of a glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and zinc oxide: the graphitized carboxylated multi-walled carbon nanotube solution is uniformly coated on the surface of the glassy carbon electrode by a drop coating method to form a stable composite film, and then the composite film is characterized by cyclic voltammetry, electrochemical impedance spectroscopy and scanning electron microscopy; Step 4: Simultaneous detection of heavy metal ions: Use differential pulse voltammetry to simultaneously detect divalent lead ions and divalent cadmium ions.

2. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) according to claim 1, characterized in that: In step 1, the particle sizes of the alumina powder after three polishings are 1.0 μm, 0.3 μm and 0.5 μm respectively, the diameter of the glassy carbon electrode is 3.0 mm, and the concentration of the sulfuric acid solution is 0.5 mol·L -1 .

3. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) according to claim 1, characterized in that: In step 3, the graphitized carboxylation multi-walled carbon nanotubes can improve the conductivity of the glassy carbon electrode, zinc oxide can enhance the electronic conductivity of the glassy carbon electrode, the multi-walled carbon nanotubes themselves have a large specific surface area, and the carboxylation treatment increases the active sites, which is beneficial to the adsorption and reaction of heavy metal ions.

4. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) according to claim 1, characterized in that: In step 4, under the optimal experimental conditions, the response peak current of divalent lead ions and divalent cadmium ions showed a good linear relationship with the concentration in the range of 25 to 450 μg / L, and the detection limits were as low as 0.535 μg / L and 0.354 μg / L, respectively.

5. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) according to claim 1, characterized in that: In the cyclic voltammetry electrochemical experiment, when an electrochemical reaction occurs on the electrode surface, the electroactive substance needs to diffuse from the bulk of the solution to the electrode surface. Assuming that the electrode reaction is a reversible single electron transfer process and the concentration distribution of the electroactive substance in the solution is only affected by the diffusion process, the basic form of the Randles-Sevcik equation can be derived through basic principles such as Fick's diffusion law and the Butler-Volmer electrode kinetic equation, as shown in the following formula: I p =2.69×10 5 n 3 / 2 AD 1 / 2 v 1 / 2 C; Among them, I p is the peak current, unit: A, n is the number of electrons transferred in the electrode reaction, A is the active area of ​​the electrode, unit: cm 2 , D is the diffusion coefficient of the electroactive substance in the solution, unit: cm 2 / s, C is the concentration of the electroactive substance in the solution, unit: mol / cm 3 , v is the scan rate set in the cyclic voltammetry experiment, unit: V / s.

6. A detection method for simultaneously detecting seawater-based Pb(II) and Cd(II) according to claim 4, characterized in that: Under the optimal experimental conditions, in the acetic acid-sodium acetate solution electrolyte dissolution with pH=6, enrichment time 300s, and enrichment potential -1.1V, the mixed sample of divalent lead ions and divalent cadmium ions was detected by differential pulse voltammetry. The response current signal in the range of 25-450μg / L, the linear regression equation of divalent lead ions was Y=0.15303X-2.8715, and the correlation coefficient was 0.99977. The linear regression equation of divalent cadmium ions was Y=0.10136X-2.478, and the correlation coefficient was 0.9988. The following detection limit calculation equation shows that the detection limits of divalent lead ions and divalent cadmium ions are 0.354μg / L and 0.535μg / L, respectively.

Citation Information

Cited By

  • Method for detecting heavy metals in water

    CN120044089A

  • Electrochemical sensing detection system and method based on bacterial nucleotide metabolism

    CN121253627A